Lemma 15.103.1. Let $A_0^\bullet \to A_1^\bullet \to A_2^\bullet \to \ldots$ be a complex of complexes of abelian groups. Assume $H^{-p}(A_ p^\bullet ) = 0$ for all $p \geq 0$. Set $A^{p, q} = A_ p^ q$ and view $A^{\bullet , \bullet }$ as a double complex. Then $H^0(\text{Tot}_\pi (A^{\bullet , \bullet })) = 0$.

Proof. Denote $f_ p : A_ p^\bullet \to A_{p + 1}^\bullet$ the given maps of complexes. Recall that the differential on $\text{Tot}_\pi (A^{\bullet , \bullet })$ is given by

$\prod \nolimits _{p + q = n} (f^ q_ p + (-1)^ p\text{d}^ q_{A_ p^\bullet })$

on elements in degree $n$. Let $\xi \in H^0(\text{Tot}_\pi (A^{\bullet , \bullet }))$ be a cohomology class. We will show $\xi$ is zero. Represent $\xi$ as the class of an cocycle $x = (x_ p) \in \prod A^{p, -p}$. Since $\text{d}(x) = 0$ we find that $\text{d}_{A_0^\bullet }(x_0) = 0$. Since $H^0(A_0^\bullet ) = 0$ there exists a $y_{-1} \in A^{0, -1}$ with $\text{d}_{A_0^\bullet }(y_{-1}) = x_0$. Then we see that $\text{d}_{A_1^\bullet }(x_1 + f_0(y_{-1})) = 0$. Since $H^{-1}(A_1^\bullet ) = 0$ we can find a $y_{-2} \in A^{1, -2}$ such that $-\text{d}_{A_1^\bullet }(y_{-2}) = x_1 + f_0(y_{-1})$. By induction we can find $y_{-p - 1} \in A^{p, -p - 1}$ such that

$(-1)^ p\text{d}_{A_ p^\bullet }(y_{-p - 1}) = x_ p + f_{p - 1}(y_{-p})$

This implies that $\text{d}(y) = x$ where $y = (y_{-p - 1})$. $\square$

In your comment you can use Markdown and LaTeX style mathematics (enclose it like $\pi$). A preview option is available if you wish to see how it works out (just click on the eye in the toolbar).